2014
DOI: 10.2310/7290.2013.00070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Positron Emission Tomographic Tracers for Imaging of Papillomavirus-Induced Tumors in Rabbits

Abstract: In this study, simultaneous positron emission tomography (PET)/magnetic resonance (MR) imaging was employed to evaluate the feasibility of the PET tracers 2-deoxy-2-18F-fluoro-d-glucose (18F-FDG), 11C-choline, and 18F-fluorothymidine (18F-FLT) to detect papillomavirus-induced tumors in an established rabbit model system. The combined PET/MR allowed the analysis of tracer uptake of the tumors using the morphologic information acquired by MR. New Zealand White rabbits were infected with cottontail rabbit papillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…862 Similar pattern uptake was also observed in rabbits to detect papillomavirus-induced tumors (Figure 172). 863 The only reported monkey study with [ 11 C]choline was performed by Friedland et al in 1983, in which brain imaging and organ biodistribution were studied. 864 [ 11 C]Choline had a rapid brain uptake followed by a rapid decline compared with other organs such as the heart, lung, liver, and kidney.…”
Section: Other Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…862 Similar pattern uptake was also observed in rabbits to detect papillomavirus-induced tumors (Figure 172). 863 The only reported monkey study with [ 11 C]choline was performed by Friedland et al in 1983, in which brain imaging and organ biodistribution were studied. 864 [ 11 C]Choline had a rapid brain uptake followed by a rapid decline compared with other organs such as the heart, lung, liver, and kidney.…”
Section: Other Compoundsmentioning
confidence: 99%
“…[ 11 C]­Choline has shown potential for assessing the degree of inflammation in atherosclerotic plaques to detect cancer (breast, colorectal, papillomavirus, prostate, and brain cancer) and pulmonary arterial hypertension . A biodistribution study of [ 11 C]­choline in normal rats showed high uptake in the kidneys, lungs, liver, and adrenal glands with a gradual decline in the uptake of these organs after 10 min p.i .…”
Section: Other Compoundsmentioning
confidence: 99%
See 1 more Smart Citation